Large B-cell lymphomas in adolescents and young adults in comparison to adult patients: a matched-control analysis in 55 patients. Issue 8 (August 2014) - Coso, Diane; Garciaz, Sylvain; Esterni, Benjamin; Broussais-Guillaumot, Florence; Ivanov, Vadim; Aurran-Schleinitz, Thérèse; Schiano, Jean-Marc; Stoppa, Anne-Marie; Chetaille, Bruno; Blaise, Didier; Vey, Norbert; Bouabdallah, Réda
Abstract The aim of our study was to assess whether large B-cell lymphoma (LBCL) in adolescents and young adults (AYA) should be considered as a clinocopathological entity, and to evaluate the prognostic value of age. Fifty-five patients aged > 15–30 years were fully matched to 365 adult patients aged 31–65 years. We found a high incidence of primary mediastinal thymic LBCL subtype (33% vs. 5%), while histological transformation was rare (2% vs. 14%). LBCL in AYA presented with a bulky mediastinal mass (51% vs. 21%), and the lactate dehydrogenase (LDH) value was significantly higher (73% vs. 54%). The complete response rate to chemotherapy was similar in the two groups. Five-year overall survival (OS) and event-free survival (EFS) of AYA were 73% and 68%, respectively. The matched-control analysis showed no difference for either OS or EFS. LBCL in AYA presents with some critical features which differ from those of older adults. However, the outcome is equivalent to that observed in older patients.